Outpatient management of pre-induction cervical ripening. (3rd August 2022) - Chen, Vicky; Sheehan, Penelope
Abstract: Introduction: Induction of labor is a common obstetric intervention. For women requiring cervical ripening, the current standard practice of inpatient labor induction can be long and challenging. Outpatient cervical ripening may be a safe and beneficial option for a select subset of low-risk pregnant women. Methods: Electronic databases were searched with specific criteria to select articles for review. The review covered literature on the safety, efficacy and acceptability of outpatient cervical ripening in the low-risk population. Discussion: Pharmacological and mechanical cervical ripening agents have been trialed in the outpatient setting. Mechanical ripening is safer than pharmacological priming, and there appears to be no disadvantage to offering outpatient catheter balloon cervical ripening to appropriately screened women who require this intervention prior to labor induction. Maternal and midwifery acceptability of outpatient care further support outpatient cervical ripening for women with low-risk pregnancies. Conclusion: The balloon catheter appears to be the optimal method for outpatient cervical ripening, but further prospective studies are required to ensure safety and benefit before it can be routinely offered to low-risk women.